Principal's Strategy in Building School Image Through Religious Character Education in SDN Wonokasian 1 - Lestiawaty Paputungan; Adi Bandono; Eni Fariyatul Fahyuni (International Consortium of Education and Culture Research Studies, 2020)
This study aims to describe the principal's strategy in building the image of the school through religious character education in SDN Negeri Wonocationan 1. This research is a descriptive qualitative study, with data sources obtained through direct observation or observation, interviews with informants and documentation. The results showed that in improving the school's image the principal's strategy was to carry out activities in instilling the values ​​of religious character, it could be classified into three activities namely (1) integration in subjects. As seen in the BTQ program that can be carried out in Islamic education teaching, (2) habituation activities can be seen from the habits that are carried out every day at school, namely the implementation of Dhuha and Dzuhur prayer in congregation, reading Asmaul Husna every morning, wearing headscarves for female students from grade 1 to grade 6, refracting smiles, greetings and greetings. (3) The last activity is a school extracurricular which includes the implementation of Istigosah, BTQ and Hadrah Al-Banjari training.